Anaerobic Fluidized Bed Treatment of Palm Oil Mill Effluent - Al-Mamun, Abdullah (1997)
A 2 m³ pilot scale anaerobic fluidized bed reactor (APBR) was designed, constructed and operated to study its ability to treat high-strength industrial wastewater, at ambient temperature. Besides performance evaluation, kinetic coefficients of three models were determined. Reactor response to pH shock load was also carried out. An early start-up of 17 days was experienced with diluted palm oil mill etlluent (POME) of 2000 mg/l COD. The hydraulic retention time (HRT) was reduced step wise from 24 hr to 4 hr which resulted in volumetric loading rates of 4.0 kgCOD/m³.d to 13.8 kgCOD/m³.d respectively. Maximum COD removal efficiencies achieved at those loading rates were between 65% and 85%. BOD and TSS removal rates were varied in the range of 64% - 91 % and 68% - 89% respectively. The raw substrate was rich in nitrogen nutrients and 17% to 55% of total nitrogen could be removed. Optimum HRT for the COD removal was found to be 1 2 hour, which was much less than that of conventional tank digester system. Reactor performance was found to be a function of loading rate, which decreased steadily with the increased loading rates. The AFBR exhibited low sludge production with sludge volume indices (SVI) of between 11 l/mg and 35 l/mg. General kinetic coefficients for Monod, Contois and Chen & Hashimoto's models were b = 0.23, Y = 0.79, µm = 4.63 and K = 2.47. Specific coefficients for Monod's model were k = 1 .22 and K. = 577, and for Contois' model, B = 0.05 and µm = 0.86. The pilot plant exhibited good buffering ability when pH shock load of 5.0 was imposed on the AFBR.